Congenital pouch colon: Is it really a rare pathology? - Cüneyt ATABEK; Suzi DEMİRBAĞ and İlhami SÜRER and Murat KOCAOĞLU and Önder ÖNGÜRÜ and Bahadır ÇALIŞKAN and Haluk ÖZTÜRK (Turkish Journal of Gastroenterology, 2019)
-